(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
This article discovered the turbulent dynamics of the Majene Port and its surrounding areas between the 1950s and the 1970s because of the seizure of the economic resources of the region by the army and guerrilla forces. The guerrillas who controlled the hinterland boycotted the flow of commodities to the army-dominated Majene Port. In response, the army fortified the city and its harbour to prevent infiltration. Army troops of Battalion 710 and the TBO imposed a trade monopoly through violence and caused suffering to people, displacing citizens from Parepare, Makassar and the islands of the Makassar Strait. Unlike other residents who were forced to leave Majene, two successful entrepreneurs, Pua Abu and Hajj Sikir, managed to overcome the constraining structures of these difficult times. As a survival strategy, the Mandar sailors and traders developed new shipping routes to the north by successfully smuggling. The present article’s elucidation of economic and political life in the port city of Majene, using a combination of archival and oral sources to reconstruct the local past, is expected to enrich the study of maritime history. Ultimately, the analysis of the obtained data revealed difficulties pertaining to regional and central interests.